A phosphorylation cascade involving ZmSnRK2.10–ZmRIPK2–ZmWRKY38 attenuates drought response by derepressing ZmSUS2 in maize - Tingting Wang; Aifang Ma; Jinkui Cheng; Yinan Han; Xuexue Chen; Tingting Fang; Ziting Zhong; Yuemei Zhang; Jikang Tian; Han Wang; Yu Wang; Junsheng Qi; et al. (Proceedings of the National Academy of Sciences, 2026)
Drought stress severely limits crop productivity, with transcription factors (TFs) playing pivotal roles in plant adaptation. Here, we identify the maize TF ZmWRKY38 as a positive regulator of drought tolerance. CRISPR/Cas9-mediated knockout of ZmWRKY38 increased plant sensitivity to drought compared with the wild type. We demonstrate that ZmWRKY38 binds to the promoter of the sucrose synthase gene ZmSUS2 and represses its transcription. Conversely, ZmSUS2 functions as a negative regulator of drought tolerance, as zmsus2 mutants displayed enhanced drought resistance. Moreover, we identified ZmRIPK2 (RPM1-induced protein kinase 2), a plasma membrane-localized receptor-like cytoplasmic kinase that also negatively regulates drought responses. Under abscisic acid (ABA) or drought stress, ZmSnRK2.10 phosphorylates and activates ZmRIPK2, triggering its partial translocation into the nucleus. Within the nucleus, ZmRIPK2 interacts with and phosphorylates ZmWRKY38, impairing its DNA-binding capacity and thereby alleviating transcriptional repression of ZmSUS2 . Together, our results reveal a negative feedback loop in which ZmRIPK2-mediated phosphorylation of ZmWRKY38 fine-tunes the drought stress response through modulation of ZmSUS2 expression. This mechanism illustrates how ABA signaling attenuates drought responses to balance stress adaptation with normal growth.